Narrow band gap conjugated polyelectrolytes for photothermal killing of bacteria1. Issue 37 (7th October 2015) - Feng, Guangxue; Mai, Cheng-Kang; Zhan, Ruoyu; Bazan, Guillermo C.; Liu, Bin
<x xml:space="preserve">Abstract</x> We report the demonstration of antimicrobial conjugated polyelectrolytes (CPEs) with high NIR absorbance for selective and efficient photothermal killing of bacteria over mammalian cells.